DFT Studies on Physicochemical Properties and Spectral Data of 2-Thiophene Carboxylic Acid Thiourea Derivatives - Andreea Neacsu; Carmellina Badiceanu; Cristina Stoicescu; Viorel Chihaia (Chemistry Proceedings)
This study focused on examining five synthesized 2-thiophene carboxylic acid thiourea derivatives that have significant pharmaceutical applications. These compounds exhibit antibacterial properties against both bacterial and fungal strains. In this study, density functional theory (DFT) calculations were performed, and the electronic properties of the investigated compounds, such as ionization potential, electron affinity, and electronic excitation energies, were calculated and compared to determine the beneficial features of these potential future medications. A vibrational analysis of the considered structures was performed, and the experimental FT-IR ATR spectra of the solid powders are presented.